2018
DOI: 10.30827/publicaciones.v48i1.7331
|View full text |Cite
|
Sign up to set email alerts
|

Interacción participativa en las clases magistrales: fundamentación y construcción de un instrumento de observación

Abstract: La pérdida de comunicación en la clase magistral sucede cuando el docente considera, quizá de forma tácita, que los contenidos vertidos son productos orales completos e ignora que, en realidad, no son entidades dadas y acabadas porque requieren de la colaboración de los estudiantes. Frente a dicha concepción, este artículo propone un encuadre conversacional como modelo dialógico de referencia en la dinámica de las clases expositivas lideradas por el docente en el aula universitaria. Situados en el dominio de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
7
Order By: Relevance
“…Narrative studies provide insights into a person's true nature and help to understand their experiences and needs (Riva et al, 2006 ). They have been used, for example, in a wide range of settings, such as secondary schools (García-Fariña, 2015 ; García-Fariña et al, 2016 ), high schools (Tronchoni et al, 2018 ), family gatherings (Gimeno et al, 2006 ), support groups for patients (Roustan et al, 2013 ), therapeutic interaction (Blanchet et al, 2005 ), and group therapy for adolescents (Arias-Pujol and Anguera, 2017 ). One of their shortcomings is that perceptibility is limited by the documentary nature of the texts, and it is not uncommon for different researchers to draw different conclusions from the same text.…”
Section: From Systematic To Indirect Observationmentioning
confidence: 99%
“…Narrative studies provide insights into a person's true nature and help to understand their experiences and needs (Riva et al, 2006 ). They have been used, for example, in a wide range of settings, such as secondary schools (García-Fariña, 2015 ; García-Fariña et al, 2016 ), high schools (Tronchoni et al, 2018 ), family gatherings (Gimeno et al, 2006 ), support groups for patients (Roustan et al, 2013 ), therapeutic interaction (Blanchet et al, 2005 ), and group therapy for adolescents (Arias-Pujol and Anguera, 2017 ). One of their shortcomings is that perceptibility is limited by the documentary nature of the texts, and it is not uncommon for different researchers to draw different conclusions from the same text.…”
Section: From Systematic To Indirect Observationmentioning
confidence: 99%
“…However, national and international empirical research has shown the advantages of pedagogical methods based in interaction, as well as on the dialogue in the classroom that occurs among students and between students and their teachers at all levels of education. Further, implementing this interaction in the classroom is demonstrably necessary in order to improve teaching quality in Upper Education (Álvarez Álvarez, 2017;De Longhi et al, 2012;Fusco, 2012;Tronchoni, Izquierdo, & Anguera, 2018;Wells, 2001).…”
Section: The Concept Of Interactionmentioning
confidence: 99%
“…The focus of this project is to demonstrate the basis and the results of the construction of an observational tool to measure the level of interaction in university classrooms since there are few academic studies directed at analysing and measuring these interactions in university classrooms (Scott et al, 2006;Tronchoni et al, 2018;Wells, 2001).…”
Section: Evaluating University Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Desde una visión antropológica, la educación facilita la rememoración (y posterior reformulación) de ciertas facultades (pre)otorgadas al ser humano en la historia (Tronchoni, Izquierdo y Anguera, 2018), porque "pone de manifi esto que el ser humano, constitutivamente, es capax symbolorum 1 , es decir, posee la aptitud, en el presente (en cada presente), para rememorar el pasado y para anticipar el futuro" (Duch, 1997, pp. 26-27).…”
unclassified